The Potential of Phage Therapy in Sepsis - Górski, Andrzej; Jończyk-Matysiak, Ewa; Łusiak-Szelachowska, Marzanna; Międzybrodzki, Ryszard; Weber-Dąbrowska, Beata; Borysowski, Jan (Frontiers in Immunology, 2017)
Sepsis remains a difficult clinical challenge, since our understanding of its immunopathology is incomplete and no efficacious treatment currently exists. Its earlier stage results from an uncontrolled inflammatory response to bacteria while in the later stage disturbed immune response with immunodeficiency syndrome develops. More than a hundred of clinical trials have not provided an efficient therapy which could ascertain an improvement or cure. Recent advancements in immunobiology of bacterial viruses (phages) indicate that in addition to their well-known antibacterial action phages have potent immunomodulating properties. Those data along with preliminary observations in experimental animals and the clinic strongly suggest that clinical trials on the efficacy of phages in sepsis are urgently needed.